MAPPING ON NEAR SURFACE ROCK PERMEABILITY ZONE BASED ON RADON CONCENTRATION DATA, LINEAMENT STRUCTURE DENSITIES, AND GEOPHYSICAL SURVEY IN PATUHA GEOTHERMAL FIELD, WEST JAVA - Ersyad, Fikriansyah
Identification of permeable zones near the surface can be conducted by mapping the presence of fractures through a combination of integrated studies from various geoscience such as remote sensing, geology, geochemistry, geophysics, and mineralogy. This study aims to extract lineaments on the surface using the modified-Segment Tracing Algorithm (m-STA) method using Digital Elevation Model (DEM) data and to model radon gas anomalies in 2D from 17 radon gas data using Geostatistical method Ordinary Kriging (OK), Ordinary Cokriging methods. (COK), and Sequential Gaussian Cosimulation (SGCS). Lineament extraction produces three lineament density maps, namely lineament frequency density map, lineament length density map, and lineament intersection density map. The three main directions of straightness are at N45°E, N70°E and N315°E. The results showed OK and COK estimates that the highest radon gas anomalies were in the north and northwest. Regionally, the spatial correlation of radon to the three types of lineament densities shows uncorrelated results, but if it is observed locally to the geological control by distribution of rock formations and determine of fault structure boundaries, radon has a very good correlation. Based on the probability map of the SGCS results for the three types of lineament densities, in general the presence of a high permeability zone is near the intersection of the fault structure and the manifestation points in the north and northwest. Areas in TTN-01, TTN-05, and TTN-03 are located in blocks with index probability close to 1 and these areas have high permeability. By Comparing of the 2D resistivity model from geophysical measurements of geoelectric and Transient Electro-Magnetic (TEM) near the manifestation, namely hot springs near the TTN-01 and TTN-05 areas in the northwest, shows a low resistivity value and these two areas are more conductive than the others. The low resistivity response values in these two areas are interpreted as the presence of an alteration product clay layer because the resistivity value is below 100 m.